Welfare effects of entry into international markets with licensing - Ferreira, Fernanda A. (2015)
We study the effects of entry of a foreign firm on domestic welfare in the presence of licensing, when the entrant is technologically inferior to the incumbent. We show that foreign entry increases domestic welfare for intermediate (respectively, sufficiently large) technological differences between the firms under licensing with fixed fee (respectively, output royalty).